2020
DOI: 10.3892/mmr.2020.11586
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the protective effect of tannic acid against arsenic trioxide‑induced cardiotoxicity in rats: Potential involvement of mitochondrial apoptosis

Abstract: arsenic trioxide (aTo) is a frontline chemotherapy drug used in the therapy of acute promyelocytic leukemia. However, the clinical use of aTo is hindered by its cardiotoxicity. The present study aimed to observe the potential effects and underlying mechanisms of tannic acid (Ta) against aTo-induced cardiotoxicity. Male rats were intraperitoneally injected with aTo (5 mg/kg/day) to induce cardiotoxicity. Ta (20 and 40 mg/kg/day) was administered to evaluate its cardioprotective efficacy against ATO-induced hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Recent studies have demonstrated that oxidative stress injury, inflammation and apoptosis of myocardial cells are potential mechanisms associated with ATO-induced cardiotoxicity, in which oxidative stress is the main cause (Chang et al, 2007;Das et al, 2010;Ye et al, 2010;Birari et al, 2020;Xue et al, 2020). Reactive oxygen species (ROS) are produced through a series of extracellular and intracellular activities, considered as a novel signalling mediator involved in cell growth, differentiation, progression and death (Sena and Chandel, 2012;Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that oxidative stress injury, inflammation and apoptosis of myocardial cells are potential mechanisms associated with ATO-induced cardiotoxicity, in which oxidative stress is the main cause (Chang et al, 2007;Das et al, 2010;Ye et al, 2010;Birari et al, 2020;Xue et al, 2020). Reactive oxygen species (ROS) are produced through a series of extracellular and intracellular activities, considered as a novel signalling mediator involved in cell growth, differentiation, progression and death (Sena and Chandel, 2012;Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Although many different oxidative damage products have been identified, 8-OHdG is an important marker defined many years ago in DNA damage. 27 Therefore, in our study, 8-OhDG expression was immunohistochemically and immunofluorescent examined in terms of DNA damage, but no difference was found between the I/R group and the groups treated with uridine in terms of 8-OHDG expression. This situation is attributed to the shortness of the I/R time or the role of a different I/R-induced oxidative stress pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Ashafaq et al have suggested the neuroprotective effects of TA in the MCAO model; however, detailed mechanisms explaining TA-mediated inhibition of inflammation or oxidative stress are lacking. A protective mechanism of TA by inhibiting NF-κB has been previously suggested in nephrotoxicity and cardiotoxicity (Jin et al, 2020 ; Xue et al 2020 ); however, the TA mechanism underlying these effects remains unclear. We speculated that the neuroprotective effects of TA were mainly derived from its chelating effect, given that TA is a water-soluble polyphenol with an 8 gallic acid group and acts as a metal chelator (Strlic et al 2002 ).…”
Section: Discussionmentioning
confidence: 98%